2016
DOI: 10.1111/aogs.12907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of additive effect of quantitative fetal fibronectin to cervical length for prediction of spontaneous preterm birth among asymptomatic low‐risk women

Abstract: Although the sensitivity improved, other predictive statistics and predictive accuracy did not improve by the addition of mid-trimester quantitative fetal fibronectin to cervical length measurement. Therefore, addition of mid-trimester quantitative fetal fibronectin to cervical length measurement cannot be recommended at this time for prediction of spontaneous preterm birth at <37(0/7)  weeks in asymptomatic low-risk women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…A study by Jwala et al. in 2016 suggested that quantitative fFN and and cervical length measurement in asymptomatic women without risk factors for PTB increase the sensitivity of fFN, but whether this is useful clinically has not been determined. A recent prospective study comparing women with a previous history of PTB with women without a history of PTB found that a positive fFN was the best predictor for recurrence of PTB, increasing the recurrence risk between two‐ to fourfold that in women without a positive fFN result .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jwala et al. in 2016 suggested that quantitative fFN and and cervical length measurement in asymptomatic women without risk factors for PTB increase the sensitivity of fFN, but whether this is useful clinically has not been determined. A recent prospective study comparing women with a previous history of PTB with women without a history of PTB found that a positive fFN was the best predictor for recurrence of PTB, increasing the recurrence risk between two‐ to fourfold that in women without a positive fFN result .…”
Section: Discussionmentioning
confidence: 99%
“…6 There is no consensus among authors regarding the value of cervical length that is considered short and the associated risk for premature labor, the reported values varying between 20 and 25 mm. [7][8][9] The importance of cervical biometry in screening patients for preterm labor has been highlighted in several publications; however, studies that have investigated the techniques of cervical measurement are rare. The evaluation of uterine cervical morphology is important because it is technically more difficult to measure cervical length in cases of curved uterine cervices, and the best measuring method in these cases is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is little evidence to support the adoption of such screening into routine clinical practice in low-risk pregnant women (150). It may have greater utility in the screening of women with other established risk factors (151153).…”
Section: “Omics” and Precision Public Healthmentioning
confidence: 99%